2008
DOI: 10.1016/j.urology.2007.10.069
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Investigation on Chronic Bladder Irritation in the Rat

Abstract: Purpose-Interstitial cystitis (IC) is a painful bladder syndrome associated with urinary frequency and urgency. Elusive etiology of IC makes its diagnosis only possible by exclusion in many cases. In the present study, we used proteomics for identifying disease-associated proteins in rat model of chronic bladder irritation.Materials & Methods-Chronic irritation of rat bladder was caused by a brief (90 secs) intravesical instillation of 0.2ml of 0.4N HCl. Whole bladders were collected at different time points a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…In order to check the specificity, we performed two-dimensional Western blot analysis using the rat aorta. As shown in figure 1, clone 75–7 recognized a single spot of 22 kDa protein at around pI 9.0, which is consistent with previously published data [25]. …”
Section: Resultssupporting
confidence: 92%
“…In order to check the specificity, we performed two-dimensional Western blot analysis using the rat aorta. As shown in figure 1, clone 75–7 recognized a single spot of 22 kDa protein at around pI 9.0, which is consistent with previously published data [25]. …”
Section: Resultssupporting
confidence: 92%
“…However, the predominant expression of S100A8-S100A9 by uroepithelial cells was an unexpected finding. Typically, these cells do not express this heterodimer complex, and its presence in the uroepithelium is normally considered to be a biomarker of immune dysregulation or neoplastic transformation (29,30). We did not detect S100A8-S100A9 expression in the uroepithelia of animals from 48 and 72 h p.i., but neutrophils were positive for S100A8-S100A9, which confirmed the efficacy of the assay.…”
Section: Discussionmentioning
confidence: 55%
“…14 Also, investigation of bladder outlet obstruction in rats showed that downregulation of transgelin might decrease bladder contractility, 15 and the study of chronic bladder irritation in rats induced by HCl drew the same conclusion. 16 The actin-binding protein, transgelin, might play a role in contractility in smooth muscle by affecting actin filament organization.…”
Section: Discussionmentioning
confidence: 99%